Human Coronavirus Infections and Pregnancy - Shangrong Fan; Shaomei Yan; Xiaoping Liu; Ping Liu; Lei Huang; Suhua Wang; Yang Pan (Wolters Kluwer Health, 2021)
Abstract. Human coronavirus (HCoV) causes potentially fatal respiratory disease. Pregnancy is a physiological state that predisposes women to viral infection. In this review, we aim to present advances in the pathogenesis, clinical features, diagnosis, and treatment in HCoV in pregnancy. We retrieved information from the Pubmed database up to June 2020, using various search terms and relevant words, including coronaviruses, severe acute respiratory syndrome coronavirus, Middle East respiratory syndrome coronavirus, 2019 coronavirus disease, and pregnancy. Both basic and clinical studies were selected. We found no evidence that pregnant women are more susceptible to HCoV infection or that those with HCoV infection are more prone to developing severe pneumonia. There is also no confirmed evidence of vertical mother-to-child transmission of HcoV infection during maternal HCoV infection. Those diagnosed with infection should be promptly admitted to a negative-pressure isolation ward, preferably in a designated hospital with adequate facilities and multi-disciplinary expertise to manage critically ill obstetric patients. Antiviral treatment has been routinely used to treat pregnant women with HCoV infection. The timing and mode of delivery should be individualized, depending mainly on the clinical status of the patient, gestational age, and fetal condition. Early cord clamping and temporary separation of the newborn for at least 2 weeks is recommended. All medical staff caring for patients with HCoV infection should use personal protective equipment. This review highlights the advances in pathogenesis, maternal-fetal outcome, maternal-fetal transmission, diagnosis and treatment in HCoV including severe acute respiratory syndrome coronavirus, Middle East respiratory syndrome coronavirus, and coronavirus disease 2019 in pregnancy.